A Linux-based IDPS using Snort. (August 2015) - Ahmed, Ghilman; Khan, Muhammad Naeem Ahmed; Bashir, Muhammad Shamraiz
Abstract : Computer networks are the backbone of enterprises and the corporate sector. Because of financial constraints, private- and public-sector corporations have shifted much of their services and business activities on to the Internet. Also, members of the general public have increased their dependence on information technology in their daily lives. This multifactor web of resources is helping organisations and the general public in their endeavours to promote businesses. Network systems deployed in an organisation communicate with other networks through the Internet for the purpose of sharing services. In addition, corporate intranets connect together through the Internet to provide services to users around the world. Financial cartels, banks, public service organisations and private business enterprises also communicate with their worldwide users over the Internet.